Subjective” and “objective’ insincerity in sociological surveys: Nonverbal manifestations - Zh V Puzanova; T I Larina (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
Insincerity of respondents in sociological research is a challenge affecting both quality of the sociological tool and the quality of the data obtained, especially features of the psychological interaction. Insincerity is information which respondents distort intentionally. However, there are two types of such insincerity - ‘objective’, i.e. a protective strategy used to deliberately hide some information, and ‘subjective’, when a respondent is forced to provide irrelevant information due to misunderstanding the question or incompetence. Nonverbal manifestations inform of thoughts and sometimes motives of respondents’ answers. In the example given in the article the ‘objective’ insincerity prevails due to the sensitive topic, while in other types of similar surveys the ‘subjective’ insincerity usually takes place too. Insincerity is not an emotion, rather a complex of cognitive attitudes and processes in a form of respond to a stimuli, but insincerity is accompanied by emotions which are the main differentiating signs of types of insincerity. Using the technology for the analysis of respondents’ nonverbal reactions in sociological research, we can identify the type of insincerity. The authors provide examples of certain emotions as reactions to specific provocative questions under the experiment and make a conclusion about the possibilities to identify not only incorrect or ‘threatening’ questions, but also the types of insincerity when answering such questions.